WORK LIFE BALANCE PADA PIMPINAN WANITA PADA PERGURUAN TINGGI SWASTA - Astuti, Rika Pristian Fitri; Mujahidin, Ali; Adelia, I'is (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to analyze the work-life balance of career women in higher education. The study employs a qualitative method and data collection techniques through interviews with participants, specifically women who have careers in private higher education institutions in the Bojonegoro district. The inclusion criteria involve women in leadership roles within both universities and faculties, working full-time, and having a minimum of one year of experience. Additionally, some of the participants have children under the age of 10, while others have children over 10. The researcher gathered data from nine participants representing three different higher education institutions, consisting of four top management individuals such as rectors and vice rectors and five middle management individuals including deans. Four of these participants have children under 10 years old, while five have children over 10 years old. The research results highlight three perspectives on work-life balance for higher education leaders: the dual role, the culture of balance, and individual strategies for managing balance